1992
DOI: 10.1002/kin.550240302
|View full text |Cite
|
Sign up to set email alerts
|

Radical processes in the pyrolysis of acetylene

Abstract: The literature on the pyrolysis of acetylene below 1000 K is reviewed and it is shown that the reaction is a radical chain polymerization initiated by H atoms. The induction period is examined and shown to arise from a rapid autocatalysis produced by the very first product, vinyl acetylene. Data from studies of acetylene polymerization induced by vinyl acetylene and styrene are examined and shown to be in good qualitative agreement with the radical chain process presented. Measured and where needed, estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 26 publications
(42 reference statements)
0
39
1
Order By: Relevance
“…Their results showed that only additions of vinylic l-C4H; and 1-C4H; radicals to ethyne were fast enough to account for the highest observed rates of benzene formation. Benzene and phenyl were formed "directly" by chemically-activated channels, These reactants and elementary reactions have also been proposed by Benson [41], Hall et al [42] and…”
Section: C2h4mentioning
confidence: 87%
“…Their results showed that only additions of vinylic l-C4H; and 1-C4H; radicals to ethyne were fast enough to account for the highest observed rates of benzene formation. Benzene and phenyl were formed "directly" by chemically-activated channels, These reactants and elementary reactions have also been proposed by Benson [41], Hall et al [42] and…”
Section: C2h4mentioning
confidence: 87%
“…Ϫ in acetylene pyrolyses, [61] and Ϫ in combustion processes, especially in fuel-rich flames and the corresponding hot waste gases. [15,54,62,63] Additionally, hexadienynes of this type have been synthesized and used as precursors for the thermal generation of 1,2,4-cyclohexatriene derivatives by the Hopf cyclization (see Section 4) and high-temperature syntheses of specially designed PAHs by FP and FVP techniques (see Sections 5Ϫ7).…”
Section: Concluding Considerationsmentioning
confidence: 99%
“…The prevailing ethyne and butadiyne (identified through their respective diagnostic bands at 730 and 627 cm À1 ) formed on the irradiation in benzene are typical products of pyrolysis [33,34] and carbonization [32] of benzene and confirm that benzene is decomposed to transient C 2 and C 4 fragments. The prevailing butadiyne (and minor C 3 H 6 and C 4 H 4 products) formed on the irradiation in ethyne were previously observed in conventional pyrolysis [32,35,36] and carbonization [37] of ethyne. Carbon monoxide being observed in all experiments indicates a reaction of carbonaceous fragments with silicon monoxide, which should resemble the known carbothermal reduction of silica [38].…”
Section: Laser Irradiation and Volatile Productsmentioning
confidence: 84%